Microstructure and properties of Fe20Co20Ni40Al20 high-entropy alloy enhanced via deep cryogenic treatment - H.M. Wang; S.S. Chou; T.T. Wu; G.R. Li; Z.J. Ji; X. Zong (Journal of Materials Research and Technology)
The Fe20Co20Ni40Al20 high-entropy alloy (HEA) exhibits a dual-phase structure composed of body-centered cubic(BCC) and face-centered cubic(FCC) crystals. This study investigates the effects of deep cryogenic treatment (DCT) at −196 °C over durations ranging from 0 to 48 h on Fe20Co20Ni40Al20 HEA synthesized via vacuum induction melting. The microstructure, mechanical properties, and fracture behavior of the alloy are comprehensively analyzed. The findings reveal that dislocations proliferate and migrate during DCT, forming dislocation tangles. High-energy dislocations generate nano-sized dislocation cell at both grain boundaries and within grains, thereby refining the microstructure of the alloy. This process transforms elongated grains into spherical fine grains, thereby enhancing both the strength and hardness of the alloy. After 36 h of DCT, the Vickers hardness of the alloy increases by 13.3 %, reaching 461.5 Vickers hardness (HV). Additionally, the tensile strength improves by 31.4 %, attaining a value of 886.2 MPa. Furthermore, the elongation of the treated alloy rises by 129 %, reaching 6.70 % compared to the untreated sample. These enhancements can be attributed to several strengthening mechanisms, including grain refinement, dislocation strengthening, the reinforcement of nano-sized dislocation cell, and second-phase strengthening. This study confirms that DCT is an effective method for improving the mechanical properties of Fe20Co20Ni40Al20 HEA.